Human Trafficking and the Relevance of Hifz al-nafs and Hifz al-’ird in Contemporary Islamic Legal Ethics - Bambang Tri Bawono; Moh. Nurul Huda; Ahmad Hadi Prayitno; Moh. Aris Siswanto (Faculty of Sharia, IAIN Metro, 2025)
Human trafficking is a profound moral crisis in today’s world, threatening human dignity and fundamental rights on a wide scale. This study explores the issue through the lens of Islamic legal ethics, focusing on the reinterpretation of hifz al-nafs (protection of life) and hifz al-’ird (protection of honor) within the framework of Maqasid al-shari’ah (the higher objectives of Islamic law). Using a normative-critical approach and drawing from both classical and contemporary sources, the research rethinks these two core principles to better respond to the complex realities of human trafficking, which often involves violence, exploitation, and human rights violations. The findings show that hifz al-nafs should not be limited to physical safety but must include psychological, social, and emotional well-being. Similarly, hifz al-’ird must go beyond the narrow notion of personal honor to protect human dignity, moral integrity, and the right to freedom from abuse. The study argues that classical Islamic legal thought needs to be revisited and updated to meet the moral and legal challenges posed by human trafficking today—by incorporating principles of justice, compassion, and human rights. This research makes an academic contribution by re-conceptualizing Maqasid al-shari’ah, especially in hifz al-nafs and hifz al-’ird, enriching the discourse on Islamic legal ethics in addressing modern social issues. It also provides a stronger theoretical basis for contemporary fiqh reform and encourages critical engagement between traditional Islamic texts and today’s ethical realities. Ultimately, this study offers a valuable reference for developing more humane, responsive, and justice-oriented Islamic legal frameworks to protect victims of human trafficking.